Proyecto de consultoría Unidad de Innovación y Desarrollo. Dirección de Ambiente y Desarrollo Sostenible. Departamento Nacional de Planeación (2020)
The DNP Environment and Sustainable Development Department is in the process of structuring an Innovation and Development Unit based on an adjusted version of the Compliance Units based on the Nesta Spiral model. The consulting team made up of 3 students from the Master's Degree in Public Management of the Universidad de los Andes carried out an analysis of the process in order to find possible deviations that did not lead to the fulfillment of the objective of improvement in Management carried out by the DNP unit and made some recommendations based on the content of the courses seen in their academic process.